(untitled) (Journal of Philosophy Culture and Political Science, 2018)
This article made an attempt to understand «what are the laws of Sharia?» and «whether they are that ballast that pulls the Muslim countries in the opposite direction from a civilization and prosperity?» as considered by large number of western scientists. The significance of the topic is a searching for a common ground between two existing and dynamically developing traditions: religious and secular, resolve conflicts arising from misunderstandings. Since the origin of Islamic religion is Saudi Arabia and its modern laws are based on the Islamic rights, a case of this country was chosen. The Kingdom of Saudi Arabia kept traditions of the Middle Ages and could modernize a modern legal framework according to them. Based on challenges of the modern society, a comparative analysis and generalization of available materials in three languages (Arab, English and Russian languages) has been chosen as a methodology of the research. The value of this work consists in an attempt to look at the problem from the different parties and to understand reasons. The practical importance of the research is to develop an effective state policy of the RK in the field of religion. Key words: the Kingdom of Saudi Arabia, sharia, transformation, comparative analysis, judicial system, sources of rights, modernization.